Wykorzystanie nowoczesnych technologii przez instytucje finansowe w procesie przeciwdziałania wykluczeniu finansowemu - Cichowicz, Ewa (Annales. Etyka w Życiu Gospodarczym, 2016)
Financial exclusion can be considered one of the important problems at the averagelevel of socioeconomic development, which includes, among others, Poland. It consistsin the presence of difficulties in accessing and/or using financial products andservices on the main market that are suitable for the needs of individuals, and preventsthem from leading a normal life in society. Due to its own characteristics andthe trends in financial markets, this phenomenon is closely linked to the issue of thedigital divide. Accordingly, it can be seen that solutions leading to the reduction ofthe financial exclusion are based on tools using information technology innovationsand modern technologies. One of the methods recognized as the most effective inthis area is financial education, which is aimed largely at children and adolescents,which justifies additionally the choice of such tools. It was equally important todetermine the extent to which modern instruments are preferred in comparison totraditional ones. The aim of this paper will be the analysis of the solutions based onmodern technologies that are used in actions taken to prevent financial exclusion inselected EU countries, including Poland. The structure of the paper is as follows:the first part will present the problem of financial exclusion (identifying groups particularlyat risk), then it will review methods of preventing and combating financialexclusion, with particular emphasis on modern ICT tools, and the final part willindicate the possible directions and barriers facing the solutions that may lead toa reduced level of financial exclusion of individuals. The method made use of indepthanalysis of the literature and a review of existing solutions, which financialinstitutions provide on the Web.